2011
DOI: 10.3382/ps.2010-00684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eggshell temperature and oxygen concentration during incubation on the developmental and physiological status of broiler hatchlings in the perinatal period

Abstract: This study evaluated the influence of incubation conditions on the developmental and physiological status of birds in the perinatal period, which spans the end of incubation until the early posthatch period. Embryos were incubated at a normal (37.8°C) or high (38.9°C) eggshell temperature (EST) and a low (17%), normal (21%), or high (25%) O(2) concentration from d 7 until 19 of incubation. After d 19 of incubation, EST was maintained, but O(2) concentrations were 21% for all embryos. Body and organ weights, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 38 publications
6
39
2
1
Order By: Relevance
“…It must be mentioned that heart hypoplasia may cause cardiac deficit and compromise chick development, resulting in the emergence of ascites during the grow-out period. Moreover, embryos derived from eggs incubated at the high temperature presented lower utilization of the yolk sac, as previously observed by Molenaar et al (2011), who obtained heavier yolk sacs in hatchlings from eggs incubated at 38.9ºC. This indicates lower chick quality and results in higher mortality during the first week due to yolk sac infections.…”
Section: Effects Of Ascorbic Acid Injection In Incubated Eggs Submittsupporting
confidence: 61%
“…It must be mentioned that heart hypoplasia may cause cardiac deficit and compromise chick development, resulting in the emergence of ascites during the grow-out period. Moreover, embryos derived from eggs incubated at the high temperature presented lower utilization of the yolk sac, as previously observed by Molenaar et al (2011), who obtained heavier yolk sacs in hatchlings from eggs incubated at 38.9ºC. This indicates lower chick quality and results in higher mortality during the first week due to yolk sac infections.…”
Section: Effects Of Ascorbic Acid Injection In Incubated Eggs Submittsupporting
confidence: 61%
“…By contrast, various experiments indicated that chicks hatched in incubation systems managed with high EST exhibited lower yolk-free body mass at hatching (Leksrisompong et al, 2007;Lourens et al, 2007;Molenaar et al, 2010a;Molenaar et al, 2011;Shim and Pesti, 2011). The differences between these results may be due to other factors in addition to temperature, such as the interaction with batches of eggs with different ages that were incubated inside the machine.…”
Section: Resultscontrasting
confidence: 40%
“…There are several studies on the effects of high incubation temperatures on in-ovo development (Wineland et al, 2000;Lekrisompong et al, 2007;Lourens et al, 2007;Molenaar et al, 2011) and on the in-ovo injection of ascorbic acid (Zakaria & Al-Anezi, 1996;Ghonim et al, 2009;Mohammed et al, 2011;Nowaczewski et al, 2012) in broilers. However, there are no studies on the in-ovo injection ascorbic acid and the subsequent submission of the eggs to heat stress during incubation.…”
Section: Introductionmentioning
confidence: 99%